Direct and indirect effects of a common cyanobacterial toxin on amphibian-trematode dynamics. (April 2019) - Buss, Nicholas; Wersebe, Matthew; Hua, Jessica
Abstract: Wildlife diseases are emerging at unprecedented rates. While there are likely several factors at play, human-mediated environmental alterations may play a significant role. Of growing interest is the effect that microcystin-LR (MC-LR), a cyanotoxin, may have on disease outcomes. In this study, using an amphibian-trematode model we examined (1) the lethal effects of MC-LR on cercariae of trematodes; (2) the sublethal effects of MC-LR exposure on the ability for trematodes to infect green frog tadpoles; and (3) the sublethal effects of MC-LR on green frog tadpole susceptibility to trematodes. We found that environmentally-relevant concentrations of MC-LR at 50, 100, and 500 μg L −1 increased cercariae rate of mortality (LC50–14h  = 134.24 μg L −1 ). However, sublethal exposure of trematodes to 2 and 10 μg L −1 MC-LR did not alter their infectivity. Conversely, sublethal exposure of tadpoles to 2 μg L −1 increased their susceptibility to trematodes by 147%. However, 10 μg L −1 of MC-LR did not affect tadpole susceptibility to trematodes, indicating a non-linear response to sublethal MC-LR exposure. Overall, our findings suggest that high concentrations of MC-LR (≥50 μg L −1 ) have the potential to limit trematode transmission to amphibian hosts through MC-LR-induced mortality. However, at lower concentrations (<10 μg L −1 ) MC-LR's effect on tadpole-cercariae disease outcome is likely driven by its effect on the tadpole host. Collectively, this work highlights the need to consider how toxicants influence both host and parasite at multiple concentrations to better understand the impacts of cyanotoxins on disease dynamics. Graphical abstract: Image 1 Highlights: Microcystin-LR is toxic to the cercariae of trematodes. Sublethal microcystin-LR exposure does not reduce trematode infectivity. Effect of microcystin-LR on tadpole susceptibility to trematodes was non-monotonic.